The objectives of Islamic banking: a maqasid approach - Mohammed, Mustafa Omar (IIUM Institute of Islamic Banking and Finance, 2009)
What should the objectives of Islamic Banking (IB) be? Unfortunately, no serious effect has been made to address this question. It has never been discussed formally. What can be seen in many literatures are scanty and disjointed discussions about avoiding riba. The absence of a careful study on the objectives of IB has resulted in misinformation and misgivings about the primary reasons for the existence of Islamic banks. As a results, most Islamic banks shy away from specifying the objectives of their establishment. This paper therefore aims at identifying the ideal objectives of IB from the theory of Maqasid al-Shari'ah and, proposes a need to develop a model of IB performance measures based on these objectives.